Chromatic Bipolar Cell Pathways in the Mouse Retina - Breuninger, Tobias (J Neurosci, 2011)
Like most mammals, mice feature dichromatic color vision based on short (S) and middle (M) wavelength-sensitive cone types. It is thought that mammals share a retinal circuit that in dichromats compares S- and M-cone output to generate blue/green opponent signals, with bipolar cells (BCs) providing separate chromatic channels. Although S-cone-selective ON-BCs (type 9 in mouse) have been anatomically identified, little is known about their counterparts, the M-cone-selective OFF-BCs. Here, we characterized cone connectivity and light responses of selected mouse BC types using immunohistochemistry and electrophysiology. Our anatomical data indicate that four (types 2, 3a/b, and 4) of the five mouse OFF-BCs indiscriminately contact both cone types, whereas type 1 BCs avoid S-cones. Light responses showed that the chromatic tuning of the BCs strongly depended on their position along the dorsoventral axis because of the coexpression gradient of M- and S-opsin found in mice. In dorsal retina, where coexpression is low, most type 2 cells were green biased, with a fraction of cells (≈14%) displaying strongly blue-biased responses, likely reflecting S-cone input. Type 1 cells were also green biased but did not comprise blue-biased “outliers,” consistent with type 1 BCs avoiding S-cones. We therefore suggest that type 1 represents the green OFF pathway in mouse. In addition, we confirmed that type 9 BCs display blue-ON responses. In ventral retina, all BC types studied here displayed similar blue-biased responses, suggesting that color vision is hampered in ventral retina. In conclusion, our data support an antagonistically organized blue/green circuit as the common basis for mammalian dichromatic color vision.